The Relationship Between Family Environment, Parenting Styles and Adolescents’ Well-Being in Cameroon - Mohamadou, Galy (2007)
The main objective of this thesis was to explore the relationship between family environment, parenting styles and adolescents’ well-being in a sample of Cameroonian adolescents. A number of factors in adolescents’ home environment are believed to influence adolescents’ well-being. A theoretical framework of the relationship between the predictor variables of family environment, parenting styles and the moderator variables of family socio-economic status (parents’ education, parents’ occupation, family income and the type of family structure) and adolescents’ sex, age, with the criterion variable of well-being (measured in terms of adolescents’ self-esteem, level of functioning and academic achievement) was constructed. Three hundred and thirty eight (338) adolescents aged between 12 to 19 years from three bilingual schools in the Adamaoua and Centre provinces in Cameroon were included in the sample. Of these respondents, (56.8%) and (43.2%) were males and females respectively. Data were collected by means of a questionnaire battery. The Family Environment Scale (FES) was used as a measure of family environmental dimensions; Buri’s Parental Authority Questionnaire (PAQ) was used as a measure of parenting styles. In addition, the General Health Questionnaire (GHQ 12), the Hare Self-esteem Scale (HSES) and school grades were used as measures of adolescents’ well-being. Data analysis uncovered three parenting styles as perceived by the adolescents using z-scores. The findings reveal no age and sex differences on measures of well-being. Majority of the adolescents (41.1%) reported having authoritative parents followed by authoritarian parents (34.6%) and only (24.3%) of the respondents viewed their parents as permissive. The results of the factor analysis revealed family environmental dimensions similar to those described by Moos and Moos. These dimensions were labelled as factor 1: supportive dimension, factor 2: growth dimension and factor 3: organized dimension. Correlations between perceived family environmental factors, parenting styles and adolescents’ well-being were investigated. The results indicated positive correlation between permissive and authoritarian parenting styles with FES conflict (r=.11) and intellectual-orientation (r=.10) subscales respectively. Authoritative parenting style did not correlate with any dimension of the family environment despite being the main style used by parents as perceived by the adolescents. Authoritarian parenting style positively correlated with adolescents’ school self-esteem (r=.14) and general level of functioning(r=.14). Permissive parenting correlated with the three domains of adolescents’ self-esteem: home(r=.20), school(r=.21) and peer(r=.22) and their general level of functioning(r=.17). General functioning correlated with measures of self-esteem. There was negative correlation between authoritarian and authoritative parenting styles (r= -.20, p<0.01). There were no gender differences in perceptions of both family environment and parenting styles by the adolescents. Significant relationships were found between parents’ characteristics and family characteristics and moderate relationships were found between family income and adolescents’ class level on the one hand, and between the type of family structure and adolescents’sex on the other. Multiple regression analysis with the FES five growth dimension subscales did not predict adolescents’ self-esteem (peer self-esteem, home self-esteem, and school self-esteem,) and level of functioning. Academic achievement however was predicted by the regression model, R2 = .032, F (5, 332) = 2.171, p<.05. The regression model with the three FES supportive dimension predicted only adolescents’ home self-esteem, R2 = .020, F (3, 334) = 2.218, p>.05, level of functioning, R2 = .22, F (3, 334) = 2.47, p<0.5 and academic achievement, R2 = .029, F (3, 334) = 4.305, p<.005. Finally the FES organized dimension did not predict adolescents’ well-being. As for the parenting styles, the regression model which included parenting styles predicted peer self-esteem, R2 = .048, F (3, 334) = 5.65, p<.001, home self-esteem, R2 = .040, F (3, 334) = 4.58, p<.005, school self-esteem, R2 = .052, F (3, 334) = 6.15, p<.0005 and level of functioning, R2 = .045, F (3, 334) = 5.25, p<.001. The regression model did not show the effects of parenting styles on academic achievement. Moderator regression analyses were performed to test the moderating effects of family socioeconomic status and adolescents’ sex, age on the relation between family environment, parenting styles and adolescents’ well-being. The interactions of these moderator variables with FES supportive, growth, and organized dimensions and authoritative, authoritarian and permissive parenting styles were partially significant. Two sub scales of FES factor 2 with income were significant for adolescents’ level of functioning but not for the other two measures of well-being. Moderator regression of family income with FES factors 1 and 3 was not significant for adolescents’ well-being. Family income moderated the relation between authoritative and adolescents’ peer self-esteem. Authoritarian (β =.50) and permissive (β =-.63) parenting styles were the best predictors of adolescents’ academic achievement as compared to authoritative and their interactions with family income were statistically significant; authoritarian t(338) = 2.35, p<0.05, permissive t(338) = -2.22, p< 0.05. Parents’ education and occupation partially moderated the relation between the predicted variables and outcome variables. The interactions between the type of family structure and parenting styles and their relation with adolescents’ well-being were not statistically significant. As for adolescents’ sex and age, their interactions with FES (growth, supportive, organized) were not significant. Sex however, did not fully moderate the relation between parenting styles and adolescents’ well-being. Overall, the study has shown the validity of the ecological perspective in that certain factors contribute to adolescents’ well-being in Cameroon and the moderating effects of certain family SES on the relationship between family environment, parenting styles and adolescents’ well-being. Future studies should include both parents and adolescents’ views in assessing the social climate of the environment, parenting styles with a more rigorous hypotheses testing.